Surface functionalization by stimuli-sensitive microgels for effective enzyme uptake and rational design of biosensor setups - Sigolaeva, Larisa V.; Pergushov, Dmitry V.; Oelmann, Marina; Schwarz, Simona; Brugnoni, Monia; Kurochkin, Ilya N.; Plamper, Felix A.; Fery, Andreas; Richtering, Walter (Polymers, 2018)
We highlight microgel/enzyme thin films that were deposited onto solid interfaces via two sequential steps, the adsorption of temperature- and pH-sensitive microgels, followed by their complexation with the enzyme choline oxidase, ChO. Two kinds of functional (ionic) microgels were compared in this work in regard to their adsorptive behavior and interaction with ChO, that is, poly(N-isopropylacrylamide-co-N-(3-aminopropyl)methacrylamide), P(NIPAM-co-APMA), bearing primary amino groups, and poly(N-isopropylacrylamide-co-N-[3-(dimethylamino) propyl]methacrylamide), P(NIPAM-co-DMAPMA), bearing tertiary amino groups. The stimuli-sensitive properties of the microgels in the solution were characterized by potentiometric titration, dynamic light scattering (DLS), and laser microelectrophoresis. The peculiarities of the adsorptive behavior of both the microgels and the specific character of their interaction with ChO were revealed by a combination of surface characterization techniques. The surface charge was characterized by electrokinetic analysis (EKA) for the initial graphite surface and the same one after the subsequent deposition of the microgels and the enzyme under different adsorption regimes. The masses of wet microgel and microgel/enzyme films were determined by quartz crystal microbalance with dissipation monitoring (QCM-D) upon the subsequent deposition of the components under the same adsorption conditions, on a surface of gold-coated quartz crystals. Finally, the enzymatic responses of the microgel/enzyme films deposited on graphite electrodes to choline were tested amperometrically. The presence of functional primary amino groups in the P(NIPAM-co-APMA) microgel enables a covalent enzyme-to-microgel coupling via glutar aldehyde cross-linking, thereby resulting in a considerable improvement of the biosensor operational stability.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Adsorption; Biosensor; Choline oxidase; Microgel; Poly(N-isopropylacrylamide-co-N-(3-aminopropyl)methacrylamide); Poly(N-isopropylacrylamideco- N-[3-(dimethylamino)propyl]methacrylamide); Quartz crystal microbalance with dissipation monitoring; Stimuli-sensitivity; Streaming potential; Surface modification